Analysis of Accountability Determination in Bireuen Regency Islamic Boarding - Naz’aina Naz’aina; Hendra Raza; Murhaban Murhaban (CV. Ridwan Publisher, 2023)
The purpose of this research is to investigate the impact of charismatic leadership, human resource competence, and the use of technology on increasing the accountability of Islamic boarding schools. The descriptive and verification methods were used in this study. In this study, the population consisted of all 164 Islamic boarding schools in Bireuen Regency. The population characteristics (sampling frame) included active Islamic boarding schools with more than 500 students. There were 33 Islamic boarding schools that fit the demographics. The sample was determined by a census. A questionnaire is the data collection instrument. Questionnaires were distributed to Islamic boarding school leaders, teachers, and accounting/administration/finance department heads. There were 99 total respondents. The collected data were analyzed using a structural equation model and a PLS approach (SEM). The findings revealed that charismatic leadership and HR competence had a positive and significant impact on accountability. While technology has no discernible positive impact on accountability.